Framing Human-Crocodile Conflict: A Quantitative Content Analysis on detik.com Online Media - Aldehead Marinda Merfonsina Uparatu; Herlina Agustin; Rinda Aunillah Sirait (LONTAR: Jurnal Ilmu Komunikasi, 2025)
Human-crocodile conflict (HCC) is an important yet under-researched aspect of human-wildlife interactions in Indonesia with significant consequences for conservation efforts and public awareness. This study used a quantitative framing method with a content analysis approach based on 168 news articles published by detik.com in 2024 to examine how human-crocodile conflict was portrayed in this one of Indonesia's leading online media. Four variables were analyzed: news source, tone, frame type, and use of thematic versus episodic framing. The findings showed a strong reliance on government sources (79.16%), with insignificant representation of non-governmental perspectives. This resulted in narrow narrative coverage. News coverage was dominated by negative reporting, particularly in government-sourced stories (sentiment score: -0.50), perpetuating fear-based stereotypes about crocodiles. The most common frames were attribution of responsibility (34.0%) and human interest (30.1%), while thematic frames were rare (14.3%), indicating a preference for episodic and event-driven reporting over systemic analysis. These patterns suggest that the media on detik.com often reinforces sensationalism at the expense of balanced conservation messages. The study underscores the need for more inclusive, science-based reporting to foster coexistence and support effective conflict mitigation.